Advanced data communications and networks - Buchanan, William (CRC Press, 2023)
Advanced Data Communications and Networks provides a comprehensive and practical treatment of rapidly evolving areas . The text is divided into seven main sections and appendices.
Includes index
Keywords: Data transmission systems; Computer networks